2005
DOI: 10.1007/bf02506127
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic influences on the environmental status of remote mountain lakes

Abstract: The special feature in this issue of Aquatic Sciences is based on work conducted as an integral part of the European Union Project "EMERGE" (European Mountain Lake Ecosystems: Regionalisation, Diagnostics and SocioEconomic Evaluation). EMERGE, which ran from 2000 to 2003 and was funded mainly by the European Commission within its Framework Programme 5 (contract EVK1-CT-1999-00032), was one of the larger EU FP5 projects devoted to environmental and climate research, with 26 partner institutes from 15 European c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Other studies undertaken on these sites are reported elsewhere (e.g. Livingstone, 2005;Marchetto & Rogora, 2004;Kernan, Catalan & Curtis, 2009a).…”
Section: Introductionmentioning
confidence: 92%
“…Other studies undertaken on these sites are reported elsewhere (e.g. Livingstone, 2005;Marchetto & Rogora, 2004;Kernan, Catalan & Curtis, 2009a).…”
Section: Introductionmentioning
confidence: 92%
“…The aquatic ecosystems are a key to global change studies, due to the sensitivity and vulnerability of their biological communities and their ecological processes (Poff et al, 2002). In order to detect trends in the climate or in ecological processes, both natural and resulting from human activity, researchers have turned to high altitude aquatic ecosystems, as sites not altered directly (Marchetto & Rogora, 2004;Livingstone, 2005). Their value as sensors of environmental change come from a series of characteristics that set them apart from other aquatic systems: low mineralization and buffering capacity, low nutrient concentration (N compounds), accumulation of trace metals and organic compounds in the food chain, and the predicted higher reaction to global warming in alpine areas (Morales-Baquero et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Bu özelliğinden dolayı, dağ göllerinin su kalitesindeki değişimlerinin izlenmesi, hava kirliliği ve iklim çalışmalarında araştırıcılara değerli bilgiler sağlamaktadır ( Livingstone 2005, Muri 2004, Muri and Brancelj 2003.…”
Section: Introductionunclassified